2013
DOI: 10.1111/ceo.12205
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐assisted subepithelial keratectomy versus epipolis laser in situ keratomileusis for myopia: a meta‐analysis of clinical outcomes

Abstract: There were no significant differences in efficacy, predictability, safety, epithelial healing time and corneal haze formation between laser-assisted subepithelial keratectomy and epipolis laser in situ keratomileusis, but the result was limited. Future more data are required to detect the potential differences between the two procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…[21] However, most studies failed to show any differences between LASEK and epi-LASIK in safety, efficacy, epithelial healing time, and corneal haze formation. [14,22,23] On the other hand, one previous study suggested LASEK provided faster visual rehabilitation and had better safety and efficacy than epi-LASIK at 3 months after operation. [24] …”
Section: Discussionmentioning
confidence: 99%
“…[21] However, most studies failed to show any differences between LASEK and epi-LASIK in safety, efficacy, epithelial healing time, and corneal haze formation. [14,22,23] On the other hand, one previous study suggested LASEK provided faster visual rehabilitation and had better safety and efficacy than epi-LASIK at 3 months after operation. [24] …”
Section: Discussionmentioning
confidence: 99%
“…48 A recent meta-analysis comparing LASEK and conventional PRK 49 concluded that uncertainty surrounds differences in efficacy, accuracy, safety and adverse effects between LASEK and PRK for eyes with low to moderate myopia. A similar conclusion was reached and published in 2010.…”
Section: Laser Ablation Algorithmsmentioning
confidence: 99%
“…Meta-analyses do 'avoid the narrative of the literature review'; however, they still require a qualitative narrative for explanations of similarities and differences found among studies and this is beyond the realm of ordinary statistics. 6 Statistics are important, but whether in analysis of basic data, or as part of meta-analysis, 'statistics serve as fallible pattern recognition devices; explanation of the origin of the observed patterns is beyond the scope of these devices'. 6 5.…”
Section: Looking Deeper Than (Just) Below the Surfacementioning
confidence: 99%